LOGISTICS 4.0 – SOLUTIONS AND TRENDS - Glistau, Elke; Coello Machado, Norge Isaias (Advanced Logistic Systems - Theory and Practice, 2019)
Logistics 4.0 means the application of Industry 4.0 in the logistics area. Therefore, many new practical and scientific solutions are created and published giving a huge amount of individual examples for realizing different logistics tasks. To find solutions in a systematic way, it is necessary to create and use meta-knowledge. The paper gives an overview about typical solution fields, the level of knowledge and application. It makes a difference between objects, processes, systems and the relevant infrastructure of logistics according the model “Smart Logistics Zone". The “Smart Logistics Zone” is defined as a scalable examination and action area for the analysis, evaluation, planning, control, regulation and (re-) configuration of logistics solutions. Basis of the research formed many years of scientific work and practical experiences in the area of logistics. This is connected with an evaluation of current scientific publications and own scientific projects on the area of Logistics 4.0. The starting points are changed requirements and conditions according to Logistics 4.0. Solutions of Logistics 4.0 are identified, systemized and described. One solution group are e.g. the possibilities of autonomously driving. They have the same idea to move, to handle and to transport without a driver or pilot realized by different means of transport. The majority of solutions of autonomous driving are on the level of prototypes and pilot projects. The new developed model “Smart Logistics Zone” is recommended to solve all tasks of logistics engineering according to Logistics 4.0 A new model is developed to systemize process knowledge. Logistics 4.0 is integrated. Important trends of Logistics 4.0 are characterized to sign the future. The theory of logistics must be further developed. Therefore, some new and improved systematics are presented in this paper: solutions of Logistics 4.0, strategies to improve logistical processes and trends of Logistics 4.0. This paper is a secondary publication of the article presented at the COMEC 2019 conference in Cuba, published with the permissions of the organization board of the conference and the authors.